2020
DOI: 10.1371/journal.pone.0237989
|View full text |Cite
|
Sign up to set email alerts
|

Surgical results in acute type A aortic dissection with preoperative cardiopulmonary resuscitation: Survival and neurological outcome

Abstract: Background Acute type A aortic dissection (ATAAD) is a life-threatening disease that requires emergent surgical intervention. This retrospective study aimed to clarify the individual characteristics, short-term and mid-term outcomes, and prognostic factors of patients who underwent surgical repair of ATAAD with preoperative cardiopulmonary resuscitation (CPR). Methods Between January 2007 and January 2020, 656 consecutive patients underwent ATAAD repair at our instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…If patients presented with hypertension or tachycardia before surgery, their hemodynamics were stabilized with intravenous beta-blockers to maintain systolic blood pressure (SBP) < 120 mmHg and a heart rate of 60–70 bpm, according to the established guidelines [ 8 ]. If patients presented with shock status, medical resuscitation and surgical rescue procedures were applied according to the standardized protocols previously reported by this institute [ 9 , 10 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…If patients presented with hypertension or tachycardia before surgery, their hemodynamics were stabilized with intravenous beta-blockers to maintain systolic blood pressure (SBP) < 120 mmHg and a heart rate of 60–70 bpm, according to the established guidelines [ 8 ]. If patients presented with shock status, medical resuscitation and surgical rescue procedures were applied according to the standardized protocols previously reported by this institute [ 9 , 10 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…A total of 51.9% of patients were diagnosed with preoperative hemopericardium according to imaging studies, 34.6% of whom presented with cardiac tamponade. In previous studies reported from this institute investigating the general ATAAD population, the incidence rates of preoperative hemopericardium and cardiac tamponade were only approximately 28–33% and 11–13%, respectively [ 12 , 15 , 28 , 29 ]. At our institute, an aggressive surgical rescue strategy was adopted for this high-risk subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified several risk factors associated with in-hospital mortality, including preoperative CPR for hemodynamic collapse. The reported incidence of preoperative CPR ranges from 3.4% to 6.8% in previous studies [ 12 , 30 , 31 ]. As a recognized preoperative risk factor for ATAAD, the early surgical mortality rate ranges from 43% to 95% [ 12 , 30 , 32 ], which is approximately three to five times higher than that of the general ATAAD population [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients' preoperative hemodynamics were stabilized with intravenous beta-blockers to maintain a systolic blood pressure < 120 mmHg and heart rate of 60-70 bpm according to the established guidelines [9]. For patients who presented with shock status, medical and surgical resuscitation procedures were applied based on the standardized protocols in this institute [10,11].…”
Section: Patient Enrollment and Preoperative Managementmentioning
confidence: 99%